Analysis of Partnership Model in DASHAT (Healthy Kitchen to Overcome Stunting) Innovation for Family Nutritional Resilience - Aqsal Falevi Harahap; Bintoro Wardiyanto; Virda Ismaliya Bangun (Yayasan Literasi Sains Indonesia, 2026)
Stunting remains a significant public health issue in Indonesia, affecting children’s physical growth and cognitive development due to chronic malnutrition. This study aims to analyze partnership models in the implementation of the DASHAT (Healthy Kitchen to Overcome Stunting) program as a public service innovation to improve household food security. The research employs a qualitative approach using a literature review method by examining empirical studies on DASHAT implementation across several regions in Indonesia, analyzed through the perspectives of New Public Governance (NPG) and New Public Service (NPS). The findings indicate that the DASHAT program effectively enhances nutritional knowledge, improves dietary behavior, and strengthens community skills in preparing nutritious meals based on local resources. Collaborative governance involving government institutions, health cadres, and communities plays a crucial role in ensuring sustainable nutrition interventions and effective information dissemination. Furthermore, the program contributes to increased family participation in fulfilling children's nutritional needs and promotes household food resilience. However, challenges persist, including limited resources, uneven mentoring quality, and suboptimal cross-sector coordination. Therefore, strengthening collaborative governance, improving human resource capacity, and ensuring consistent program implementation are essential to enhance the effectiveness and sustainability of DASHAT in reducing stunting rates.